Prevalence and Risk Factors for Iron Deficiency Anemia and Iron Depletion During Pregnancy: A Prospective Study - Gomes da Costa, Ana; Vargas, Sara; Clode, Nuno; M. Graça, Luís (Acta Médica Portuguesa, 2016)
Introduction: Anemia and iron deficiency during pregnancy are a worldwide concern and are more frequent among women of reproductive age, pregnant women, and young children. The aim of this study was to assess the prevalence of iron deficiency anemia and the risk factors for iron depletion during the first half of pregnancy, in a Portuguese population. Material and Methods: A prospective study was conducted at a tertiary hospital and included pregnant women, until the 20th week of gestation. Data was collected regarding demographic and pregnancy features and hemoglobin and serum ferritin concentrations were determined. A multivariate logistic regression was performed to identify potential risk factors for iron deficiency. Results: Two hundred and one women were included, from which five (2.49%) presented anemia. Additionally, 77 (38.3%) exhibited iron deficiency and 22 (10.9%) revealed severe iron depletion. Maternal age was the only risk factor identified. The odds ratio (OR) was equal to 12.99 (95% CI 2.41 - 70.0) for women under twenty years of age and 2.09 (95% CI 1.05 - 4.14) for women older than thirty years of age. Discussion and Conclusion: The prevalence of maternal anemia in the first half of pregnancy was lower than in other studies. However, more than one-third of the women exhibited iron deficiency. With the exception of maternal age, no other risk factors were identified.